Effectiveness of home respiratory polygraphy for the diagnosis of sleep apnoea and hypopnoea syndrome. Issue 7 (20th May 2011) - Masa, Juan F; Corral, Jaime; Pereira, Ricardo; Duran-Cantolla, Joaquin; Cabello, Marta; Hernández-Blasco, Luis; Monasterio, Carmen; Alonso, Alberto; Chiner, Eusebi; Rubio, Manuela; Garcia-Ledesma, Estefania; Cacelo, Laura; et al.
Abstract : Introduction: Home respiratory polygraphy (HRP) may be a cost-effective alternative to polysomnography for the diagnosis of sleep apnoea-hypopnoea syndrome (SAHS), but stronger evidence is needed. Normally, patients transport HRP equipment from the hospital to home and back, which may create difficulties for some patients. Objectives: To determine both the diagnostic efficacy and cost of HRP (with and without a transportation service moving the device and telematic transmission of data) in a large sample compared with in-hospital polysomnography. Methods: Patients suspected of having SAHS were included in a multicentre study (eight hospitals). They were assigned to home and hospital protocols in random order. Receiver operating characteristic curves were constructed for manual respiratory polygraphy scoring protocol and different polysomnographic cut-off points. Diagnostic efficacies for several polysomnographic cut-off points were explored and costs for two equally effective alternatives were calculated. Results: Of 366 randomised patients, 348 completed the protocol. The best receiver operating characteristic curve was obtained with a polysomnographic cut-off of the apnoea-hypopnoea index (AHI)≥5. The sensitive HRP AHI cut-off point (<5) had a sensitivity of 96%, a specificity of 57% and a negative likelihood ratio (LR) of 0.07; the specific cut-off (>10) had a sensitivity of 87%, a specificity of 86% and a positive LR of 6.25. The cost of HRP was half that of polysomnography. Telematic transmission costs were similar if the patients' costs were taken in to account. Conclusion: HRP is an alternative to polysomnography in patients with suspected SAHS. Telematic procedures may help patients with limited mobility and those who live a long way from the sleep centre.